PERAN GURU DALAM MEMBENTUK KARAKTER DISIPLIN ANAK USIA 4-5 TAHUN DI TK SHINING KIDS SCHOOL PALANGKA RAYA - Rosita; Yoan Colina; Della Gita Van Gobel (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the critical role of teachers as primary models in shaping children's disciplined character at school, particularly for children aged 4-5 years who are in a phase of spontaneous imitation. Observations at K4A class of Shining Kids School Palangka Raya revealed that the development of disciplined character was not yet optimal. Children struggled to wait for their turn, were unable to complete tasks on time, and left eating utensils at the dining area. These conditions indicate that children require teacher-led approaches and guidance. This study aims to describe the teacher's role in shaping the disciplined character of children aged 4-5 years in class K4A and to identify the factors influencing the formation of disciplined character at Shining Kids School Palangka Raya. This study utilized a qualitative approach with a descriptive design. Information was gathered through observation, interviews, and documentary analysis. The research findings indicate that K4A teachers carry out their roles optimally through five aspects: (1) providing exemplary behavior characterized by responsibility, authority, independence, and discipline; (2) providing practice and guidance; (3) providing encouragement; (4) conducting assessments; and (5) designing lesson plans. Furthermore, the formation of disciplinary character is influenced by internal factors, including children's health and parenting styles, as well as external factors, such as the availability of school facilities (lockers, shoe racks, and sinks) and peer influence.